A Comparative Study on the Flexural strengths of RMGIC and Cention N andEvaluation of their Shear Bond Strengths with Composite: An In Vitro Study - Mandeep Kaur; Ashwath Kumar V; Salil .; Angeline Jose; Ashu K Gupta; Anshu Minocha (RGUHS Journal of Dental Sciences)
BackgroundnbspCention N a recently introduced restorative material in Malaysian healthcare was evaluated in this study to compare its properties with other commonly used materials.nbspObjectivenbspThis study was conducted to compare the flexural strength of RMGIC and Cention N and evaluate their shear bond strength when bonded with composite resins. nbspMethodsnbspTo assess flexural strength ten rectangular test bars were fabricated-divided into Group 1 Cention N and Group 2 RMGIC-and subjected to a three-point bending test. For evaluating shear bond strength twenty acrylic blocks were prepared and grouped as Group A Cention N bonded to composite and Group B RMGIC bonded to composite then tested with a Universal testing machine.nbspResultsnbspGroup 1 Cention N demonstrated the highest average flexural strength while Group A recorded the greatest shear bond values when bonded to composite. Both strength values were significantly higher compared to their RMGIC counterparts. nbspConclusionnbspCention N exhibited superior flexural and shear bond strength properties compared to RMGIC.